2016
DOI: 10.1155/2016/9597579
|View full text |Cite
|
Sign up to set email alerts
|

LISP Optimisation of Mobile Data Streaming in Connected Societies

Abstract: Mobility mechanisms are key elements of “always connected” smart environments. Since the first mobile IPv4 protocols, the IP mobility solutions have evolved from host mobility to network mobility and migration to IPv6, but there are still use-cases to be covered, especially for redundant multihomed scenarios. Also mobility does not refer only to hosts or individuals, but also to code/applications and to virtual machines. LISP (Locator/Identifier Separation Protocol) can contribute to new solutions for both hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Our results are in agreement with other studies which showed that the exposure to acidic drinks and food intake induces the chemical dissolution of restorative materials, thus increasing the roughness of the superficial layer. Some studies have shown that a residual surface roughness may induce bacterial plaque retention [19][20][21]. pH of Coca-Cola is very low.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with other studies which showed that the exposure to acidic drinks and food intake induces the chemical dissolution of restorative materials, thus increasing the roughness of the superficial layer. Some studies have shown that a residual surface roughness may induce bacterial plaque retention [19][20][21]. pH of Coca-Cola is very low.…”
Section: Resultsmentioning
confidence: 99%
“…The control module is configured using a static configuration file which is read during boot-up. At run-time, it is possible to modify parts of this configuration remotely thanks to the NETCONF (RFC 6241) module that OOR implements with the libnetconf library 11 . Other major auxiliary modules are described in this section.…”
Section: Multi-platformmentioning
confidence: 99%
“…Currently, there are other academic initiatives (e.g., [11]) that are making use of the project for their own research. Furthermore, OOR has helped to discover new research challenges that need to be addressed.…”
Section: B Use-cases For Oormentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our previous work we have implemented a simulated demonstrator based on Cisco devices supporting LISP [47] in order to demonstrate the benefits of LISP compared to other routing protocols but also to validate security and load-balancing solutions. The demonstrator, part of our previous work, was illustrative for the LISP configuration and functionality and can be applied for several scenarios, from distributed enterprise offices to the mobility use-cases, ensuring encrypted communications, failover mechanisms, and load-balancing in an emulated enterprise environment.…”
Section: Lisp Implementation Of Ran Multihoming and Load-balancing Fomentioning
confidence: 99%